The menstrual cycle regularity and skin: irregular menstrual cycle affects skin physiological properties and skin bacterial microbiome in urban Chinese women - Laiji Ma; Hong Jiang; Tingting Han; Yanqin Shi; Man Wang; Shanshan Jiang; Suzhen Yang; Lingyun Yao; Qingwen Jia; Li Shao (BMC, 2023)
Abstract Background The regularity of the menstrual cycle directly affects women's health. Many studies have focused on menstrual health; however, menstrual cycle regularity-related variations in skin physiological characteristics and skin microbiota have been seldom investigated. Methods To investigate the menstrual cycle regularity-related variations in skin physiological characteristics and skin microbiota of 197 cases of Chinese women aged 18-35 years living in shanghai in 2021. Based on a self-evaluation questionnaire, the volunteers were divided into three groups C1 (those with a regular menstrual cycle), C2 (those with a less regular menstrual cycle) and C3 (those with an irregular menstrual cycle). The physiological parameters of facial skin were measured by non-invasive methods and the skin microbiome was analyzed by 16S rRNA high-throughput sequencing. Results In the C3 group, the hydration content was significantly decreased (p < 0.05), the TEWL was significantly increased (p < 0.05), and the sebum content was increased (p > 0.05), indicating that the skin barrier integrity weakened with increased menstrual cycle irregularity. Additionally, the melanin level, L value and b value were significantly decreased (p < 0.05) in the C3 group, but the a value was significantly increased (p < 0.001), which indicated that the skin color became darker. Furthermore, the skin microbiota diversity decreased with increasing cycle irregularity, but the differences were not significant. The skin microbiota composition showed that the proportion of Firmicutes, Acinetobacter, Staphylococcus and Cutibacterium were increased in those with an irregular menstrual cycle, indicating that alterations in the ratio of bacterial phyla and/or genera might disturb skin homeostasis. Spearman correlation analysis revealed strong correlations between the microbiota and skin physiological parameters. Based on the associations among hormones, skin physiological parameters and skin microbiota, it is possible that the skin physiological parameters, as well as the skin microbial diversity and composition, change with hormonal fluctuations during the menstrual cycle. Conclusions An irregular menstrual cycle can affect skin physiological characteristics and the skin microbiota. Female with an irregular menstrual cycle should strengthen skin care practices and use skin care products with moisturising and soothing effects to protect their skin.